ANALISIS “THE ART OF WAR” BUAH KARYA SUN TZU DALAM PERSPEKTIF KEPEMIMPINAN HINDU - I Dewa Gede Darma Permana (Sanjiwani: Jurnal Filsafat, 2025)
In this time of global competition, it is important for everyone to have leadership skills. Leadership principles are needed to be able to be a guideline for managing oneself and others, without leaving the noble elements of morality. One of the leadership guidelines that can be used as a reference is Sun Tzu's “The Art of War”. In line with the teachings in Hindu Leadership, both are based on the noble values of religion and culture. Considering these similarities, researchers in this case tried to examine The Art of War in the perspective of Hindu Leadership, with the main objective of presenting correlations and noble leadership guidelines that can be empowered in life. Through methods based on philosophical hermeneutics, and balanced with interactive analysis from Miles and Huberman, this research obtained several findings, including: 1). The essence of Sun Tzu's The Art of War is a guideline and philosophy of leadership that unites Taoism with strategies or tactics of warfare. 2). The urgency of Hindu leadership in the era of disruption as a noble guideline to maintain religious and cultural values. 3). In terms of analysis, there is a correlation between The Art of War which is studied in terms of Hindu Leadership concepts, both regarding the importance of planning, mind control, and negotiation skills.